Visualization of fields and applications in engineering - Tou, Stephen (Chichester, U. K. : John Wiley & Sons, 2011)
'Visualization of Fields and Applications in Engineering presents the basic techniques for tensor field visualization and mapping from an engineering approach. Focusing on the fundamental aspects of post processing databases and applications, the author explores existing theories and their integration in tensor field visualization and analysis. Examples cover a variety of problems from mechanical, civil to electrical engineering with applications beyond and across many disciplines. The subject is presented logically from fundamental theories to integrated, multi-disciplinary technologies with practical applications in engineering, computer sciences and visual/general sciences. Driven by computer technology, the analysis of transport phenomena has developed rapid and extensively in recent times and it is timely to introduce the subject from an engineering viewpoint. The materials are suitable for a senior/graduate course and to serve as a source of reference for those who work in engineering/science professions or in pursuit of academic training/research. Offers a unique engineering approach to basic techniques for tensor field visualization and mapping. Collates together material currently disseminated throughout the literature into one accessible point of reference. Explores a variety of sample problems from mechanical, civil to electrical engineering with applications beyond and across many disciplines.'--
'Visualization of Fields and Applications in Engineering presents the basic techniques for tensor field visualization and mapping from an engineering approach'--
Includes bibliographical references and index.
Keywords: Engineering mathematics; Fluid dynamics -- Mathematics; Electromagnetic fields -- Mathematical models; Gravitational waves -- Mathematical models; Information visualization